2023
DOI: 10.1002/nvsm.1793
|View full text |Cite
|
Sign up to set email alerts
|

Four lessons learned: Employees' perceptions of fundraising via reward‐based crowdfunding

Abstract: An innovative way to support cultural institutions is through reward-based crowdfunding, an online funding mechanism for a specific project, which offers donors a reward for their donation. We explored employees' perceptions of crowdfunding and focused on the question: "How do employees of cultural institutions running a crowdfunding campaign perceive the use of crowdfunding to collect funds?" To answer this question, we focus on interpretive research using semi-structured interviews (n = 15) among Dutch cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Crowdfunding is mostly characterized by network‐based fundraising (Van Teunenbroek & Hasanefendic, 2022; Van Teunenbroek & Smits, 2022), as initiators are often close to donors (Borst et al, 2018; Dalla Chiesa, 2022). Therefore, we argue that people are likelier to donate to a crowdfunding project with a strong tie than a weak one (Tosatto et al, 2022)—the latter representing only casual contacts (Haythornthwaite, 2005).…”
Section: Crowdfunding Features and Mechanisms Impacting Giving Behaviormentioning
confidence: 99%
See 3 more Smart Citations
“…Crowdfunding is mostly characterized by network‐based fundraising (Van Teunenbroek & Hasanefendic, 2022; Van Teunenbroek & Smits, 2022), as initiators are often close to donors (Borst et al, 2018; Dalla Chiesa, 2022). Therefore, we argue that people are likelier to donate to a crowdfunding project with a strong tie than a weak one (Tosatto et al, 2022)—the latter representing only casual contacts (Haythornthwaite, 2005).…”
Section: Crowdfunding Features and Mechanisms Impacting Giving Behaviormentioning
confidence: 99%
“…Intangible rewards excel in providing a connection with a charity (Bitterl & Schreier, 2016; Hobbs et al, 2016; Van Teunenbroek & Smits, 2022). Running multiple experiments, Bitterl and Schreier (2016) found that donors connect strongly with a project by donating rather than buying a product.…”
Section: Crowdfunding Features and Mechanisms Impacting Giving Behaviormentioning
confidence: 99%
See 2 more Smart Citations